Gamow-Teller excitations at finite temperature: Competition between pairing and temperature effects - Yuksel, E.; Paar, N.; Colo, G.; Khan, E.; Niu, Y. F. (AMER PHYSICAL SOC, 2020)
The relativistic and nonrelativistic finite temperature proton-neutron quasiparticle random phase approximation (FT-PNQRPA) methods are developed to study the interplay of the pairing and temperature effects on the Gamow-Teller excitations in open-shell nuclei, as well as to explore the model dependence of the results by using two rather different frameworks for effective nuclear interactions. The Skyrme-type functional SkM* is employed in the nonrelativistic framework, while the density-dependent meson-exchange interaction DD-ME2 is implemented in the relativistic approach. Both the isoscalar and isovector pairing interactions are taken into account within the FT-PNQRPA. Model calculations show that below the critical temperatures the Gamow-Teller excitations display a sensitivity to both the finite temperature and pairing effects, and this demonstrates the necessity for implementing both in the theoretical framework. The established FT-PNQRPA opens perspectives for the future complete and consistent description of astrophysically relevant weak interaction processes in nuclei at finite temperature such as beta decays, electron capture, and neutrino-nucleus reactions.
Keywords: SHELL-MODEL; NUCLEI; FLUCTUATIONS; RESONANCES; ISOSCALAR; SPIN; GAPS; MASS; Physics